How supplier relationship management practices affect the performance of organizations. A case of Ghana cocoa board within Brong-Ahafo region - Biatey Abedi Richmond (KNUST, 2024)
A thesis submitted to the department of supply chain and information systems of the Kwame Nkrumah university of science and technology school of business, in partial fulfilment of the requirements for the award of the degree of master of science in (logistics and supply chain management option)